2023
DOI: 10.1111/jnc.15910
|View full text |Cite
|
Sign up to set email alerts
|

JAG‐1/Notch signaling axis in the spinal cord contributes to bone cancer pain in rats

Abstract: Notch signal plays an important role in regulating cell–cell interactions with the adjacent cells. However, it remains unknown whether Jagged1 (JAG‐1) mediated Notch signaling regulates bone cancer pain (BCP) via the spinal cell interactions mechanism. Here, we showed that intramedullary injection of Walker 256 breast cancer cells increased the expression of JAG‐1 in spinal astrocytes and knockdown of JAG‐1 reduced BCP. The supplementation of exogenous JAG‐1 to the spinal cord induced BCP‐like behavior and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…A CIBP model was created by injecting 10 μL Walker-256 breast cancer cell suspension into the bone marrow cavity of the left tibia of Sprague-Dawley rats. 22 , 23 , 24 Our previous research identified the widespread distribution of ac4C in the spinal dorsal horn (SDH) L4–L6 transcriptome of rats by ac4C-specific RNA immunoprecipitation assay (acRIP-seq). The differential genes with ac4C mRNA modification and mRNA expression in CIBP rats revealed a significant correlation, suggesting that ac4C is involved in the development of CIBP.…”
Section: Introductionmentioning
confidence: 99%
“…A CIBP model was created by injecting 10 μL Walker-256 breast cancer cell suspension into the bone marrow cavity of the left tibia of Sprague-Dawley rats. 22 , 23 , 24 Our previous research identified the widespread distribution of ac4C in the spinal dorsal horn (SDH) L4–L6 transcriptome of rats by ac4C-specific RNA immunoprecipitation assay (acRIP-seq). The differential genes with ac4C mRNA modification and mRNA expression in CIBP rats revealed a significant correlation, suggesting that ac4C is involved in the development of CIBP.…”
Section: Introductionmentioning
confidence: 99%